PENITENSIER DALAM PERSPEKTIF HAK ASASI MANUSIA - Zahratul Ain Taufik; Ayu Riska Amalia; Atika Zahra Nirmala (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2023)
Abstract The protection of human rights is not only attached to the individual human being, but also to other human beings. This is a consequence of humans as social beings who cannot be separated from other humans. Criminal Law is then present to regulate various acts that violate human rights which will then be punished. Criminal law, of course, cannot be implemented properly if there are no other legal sciences that accompany it, including Penitentiary law, which is known as the Law of Punishment or legal science that studies punishment. Penitentiary law is not a rule of law that can immediately punish criminals arbitrarily, but needs to consider human rights. This paper focuses on whether penitentiary law violates human rights or not. The purpose of this paper is to examine penitentiary law from a human rights perspective. This writing uses normative legal research methods with literature research techniques that are analyzed qualitatively using a statutory approach and conceptual approach. The results of the study concluded that Penitentiary Law is a rule that seeks to continue to fight for the human rights of people who have been violated by the perpetrator of the crime by punishing him, but the model of punishment given still takes into account the human rights of the convicted criminal. keywords: Human Rights, Criminal Law, Penitentiary Law